Assédio moral na universidade: descrição de contexto e propostas de enfrentamento - Morais, Ysabelly Nascimento da Nóbrega (2021)
This research describes the context of bullying at the Federal University of Paraíba from the perception of servers and proposes the institution measures to confront. The study revealed psychosocial risks and situations of bullying, as well as getting to know the perceptions of public servants about the university's performance in the face of the problem and appraising actions they considered useful to contain bullying in the institution. The collected data were obtained through the application of questionnaires and interviews. The results found showed that more than half of the employees identify themselves as victims of psychological harassment and that at least 70% of them consider harassment a common problem at the university. The servers also considered the institution's performance to be insufficient to remedy the phenomenon and suggested, among other actions, the reception of victims and the dissemination of information about moral harassment. This work also built a normative resolution and an informative booklet as proposals for preventing and combating the institution.